2014
DOI: 10.2169/internalmedicine.53.2208
|View full text |Cite
|
Sign up to set email alerts
|

The Accuracy and Uncertainty of a Sheet-type Portable Monitor as a Screening Device to Identify Obstructive Sleep Apnea-hypopnea Syndrome

Abstract: Objective Laboratory-based polysomnography (PSG) is the gold standard for diagnosing obstructive sleep apnea-hypopnea syndrome (OSAHS), but it is expensive and requires overnight hospitalization. Recently, a sheet-shaped breath detection monitor, the SD-101, has been developed, and several reports have so far demonstrated the screening accuracy of this device. The aim of this study was to assess the accuracy and the uncertainty of this device. Methods A total of 101 suspected OSAHS patients underwent simultane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…Therefore, we compared the screening accuracy of REI_eTST with that of REI_TIB according to the OSA severity cut-off levels. In particular, the sensitivity and specificity of non-wear PM devices for predicting severe OSA (AHI ≥ 30 events/h) have not been reported previously (13)(14)(15)(16)(17). However, in the present study, both REI_eTST and REI_TIB measured with the SBV showed relatively high sensitivity and specificity at optimal cutoff values for predicting OSA with all three criteria (AHI ≥ 30, AHI ≥ 15, AHI ≥ 5), Moreover, data loss in PM recording using wearable sensors such as oronasal and respiratory effort sensors is considered an important problem (11).…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Therefore, we compared the screening accuracy of REI_eTST with that of REI_TIB according to the OSA severity cut-off levels. In particular, the sensitivity and specificity of non-wear PM devices for predicting severe OSA (AHI ≥ 30 events/h) have not been reported previously (13)(14)(15)(16)(17). However, in the present study, both REI_eTST and REI_TIB measured with the SBV showed relatively high sensitivity and specificity at optimal cutoff values for predicting OSA with all three criteria (AHI ≥ 30, AHI ≥ 15, AHI ≥ 5), Moreover, data loss in PM recording using wearable sensors such as oronasal and respiratory effort sensors is considered an important problem (11).…”
Section: Discussionmentioning
confidence: 83%
“…These issues can be resolved by PM recording without the need for attaching sensors, i.e., non-wear PM devices. Previous studies on the validity of OSA screening with non-wear PM devices, such as a static charge sensitive bed (SCSB) (13,14) and a sheet-shaped device placed on a mattress (15)(16)(17), have been conducted. However, due to the insufficient number of validation studies, these devices have been classified as type 4 PM for the screening of OSA, and have hence not been generally accepted (9,11).…”
Section: Introductionmentioning
confidence: 99%
“…In the study by Agatsuma et al (14), ROC curve analysis of aa respiratory disturbance index (measured by SD-101, Kentzmedico Co. Ltd, Saitama, Japan) of 14 events/h revealed 89.5% sensitivity and 85.8% specificity for identifying OSA. Tsukahara et al (15) calculated AHI using the time in bed, and at a cut-off of 14 events/h, the sensitivity and specificity of detecting an AHI of ≥20 events/h were 90.2 and 90.0%, respectively. Kobayashi et al (16) used the SD-101 with percutaneous oxygen saturation detecting an AHI of >15 events/h on PSG with a sensitivity (specificity) of 96.9% (90.5 %) compared with 87.5% (85.7 %), respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Three assessed the SD-101 sensor (Tsukahara et al, Agatsuma et al, and Takasaki et al). [23][24][25] All six studies, including Beattie et al, evaluated devices that used, at a minimum, several pressure sensors that measured respiratory and body movement to estimate AHI. 26 Norman et al evaluated a device that also measured acoustic features, 27 and Tenhunem et al additionally measured heart rate.…”
Section: Bed/mattress-based Sensorsmentioning
confidence: 99%
“…Of the six studies, one (Tsukahara et al 23 ) was not included in the quantitative analysis because we were not able to obtain the true positive, true negative, false positive, and false negative values. A forest plot of the five remaining studies is shown in Figure 2.…”
Section: Bed/mattress-based Sensorsmentioning
confidence: 99%